A clip‐based protocol for breast boost radiotherapy provides clear target visualisation and demonstrates significant volume reduction over time. Issue 3 (23rd June 2015) - Lewis, Lorraine; Cox, Jennifer; Morgia, Marita; Atyeo, John; Lamoury, Gillian
Abstract Introduction The clinical target volume (CTV) for early stage breast cancer is difficult to clearly identify on planning computed tomography (CT) scans. Surgical clips inserted around the tumour bed should help to identify the CTV, particularly if the seroma has been reabsorbed, and enable tracking of CTV changes over time. Methods A surgical clip‐based CTV delineation protocol was introduced. CTV visibility and its post‐operative shrinkage pattern were assessed. The subjects were 27 early stage breast cancer patients receiving post‐operative radiotherapy alone and 15 receiving post‐operative chemotherapy followed by radiotherapy. The radiotherapy alone (RT/alone) group received a CT scan at median 25 days post‐operatively (CT1rt) and another at 40 Gy, median 68 days (CT2rt). The chemotherapy/RT group (chemo/RT) received a CT scan at median 18 days post‐operatively (CT1ch), a planning CT scan at median 126 days (CT2ch), and another at 40 Gy (CT3ch). Results There was no significant difference (P = 0.08) between the initial mean CTV for each cohort. The RT/alone cohort showed significant CTV volume reduction of 38.4% (P = 0.01) at 40 Gy. The Chemo/RT cohort had significantly reduced volumes between CT1ch: median 54 cm3 (4–118) and CT2ch: median 16 cm3, (2–99), (P = 0.01), but no significant volume reduction thereafter. Conclusion Surgical clips enable localisation of the post‐surgical seroma for radiotherapy targeting. Most seroma shrinkage occurs early, enabling CT treatment planning to take place at 7 weeks, which is within the 9 weeks recommended to limit disease recurrence.